’Healing the Land’ in the Canadian Arctic: Evangelism, Knowledge and Environmental Change - Johnson, Noor (Journal for the Study of Religion, Nature and Culture, 2012)
Beginning in 2006, an evangelical movement called ‘Healing the Land’ was introduced to a number of Inuit communities in the Canadian Arctic. Healing the Land (HTL), which promoted an ethic of environmental stewardship through prayer and repentance of sin, also helped Inuit make sense of rapid environmental change. Rather than linking shifts in weather and plant and animal distributions to climate change, HTL leaders argued that they resulted from communal processes of prayer and repentance that miraculously restored the environment to an Edenic state of plenty. In this article, I explore the appeal of HTL’s theology and ritual practice to Inuit residents of Clyde River, Nunavut. I argue that residents found HTL’s explanations of environmental change compelling because HTL offered a vision of integrated action through which individuals and communities could address social and environmental issues simultaneously.